Application To Classify The Population Census The Total Population By Level Of Education Using K-Means Clustering Algorithm: Application To Classify The Population Census The Total Population By Level Of Education Using K-Means Clustering Algorithm - Dewi Janetta Az Zahra; Agung Triayudi; Ira Diana Sholihati (Jurnal Mantik, 2020)
The current population census is still Carried out by visiting each house. With a process like this, it will take a lot of time so that it will have an impact on the number of costs incurred by the government. For this reason, an online application is needed to Facilitate officers in conducting population censuses. Also, through this population census, the Researchers conducted a grouping of education levels intending to find out the population based on their level of education. The method used is the k-means clustering algorithm. There are three groupings items, namely C1 = population at a high level, C2 = population at a moderate level and C3 = population at a moderate level. The final centroid value used at C1 = (4.8000000,959.20000), C2 = (4.00000,854.000000) and C3 = (9.00000,668.00000). So that the results Obtained grouping C1 = RW2, RW7 and RW8,